Extraction of Fronto-orbital Metallic Radio Antenna Through Stallard Orbitotomy. (April 2013) - Elia, Maxwell D.; Kombo, Ninani; Abbed, Khalid; Levin, Flora; Servat, Juan J.
ABSTRACT A 39-year-old man presented after falling on a radio antenna while in his yard. Computed tomography revealed that the antenna entered the right superolateral orbit, penetrating through the right orbital roof and extending into the right frontal lobe. A Stallard orbitotomy was performed to remove the antenna resulting in blepharoptosis.